INFLUENCE OF POLLUTION BY HEAVY METALS ON BIOLOGICAL PROPERTIES OF MOUNTAIN CHERNOZEMS OF THE SOUTH OF RUSSIA - S. I. Kolesnikov; M. V. Yaroslavtsev; N. A. Spivakova; K. S. Kazeev; T. V. Denisova; E. V. Dadenko (Юг России: экология, развитие)
Pollution of the chernozem typical (mountain) Cr, Cu, Ni and Pb oxides leads to deterioration of its condition: activity of a catalase and dehydrogenase decreases, cellulolytic activity, an abundance of bacteria of the sort Azotobacter, worsen indicators of germination and initial growth of a garden radish. Extent of decrease depends by nature metal and its concentration in the soil. The studied TM oxides form the following row on extent of negative impact on biological properties of the chernozem of typical (mountain): CrO3> CuO> = PbO> = NiO.